Telmisartan Spongelike Particles as Oral Capsule II: Factors Affecting Formulation - Hussam H. Tizkam (Journal of Global Pharma Technology, 2016)
Telmisartan  (TEL) is selective angiotensin II receptor blocker sued in the management of cardiovascular disorders. It is a class II drug according to Biopharmaceutics Classification System (BCS). The aim of current study is to prepare TEL sponge like particles (SP) as a drug delivery system and investigate the different variables that may affect the formulation in order to enhance the solubility and dissolution rate thereof. The TEL SP formulations were prepared by quasi-emulsion solvent diffusion method using Eudragit E100 as SP forming polymer at drug: polymer ratio of (5:1). The effect of solvent type of internal phase, internal phase volume, stirring rate, stirring time, plasticizer concentration, surfactant concentration, external phase volume, and drying temperature on the formulation of TEL SP were investigated. Twenty five TEL SP formulations were prepared and filled into hard gelatin capsule. They were investigated and characterized for production yield, loading efficiency and in vitro drug release in 0.1N HCl (pH 1.2). Results showed that the best TEL SP formula was F15 which was prepared using 5ml of dichloromethane (DCM) as an internal phase solvent, 0.05 g of polyvinyl alcohol (PVA) as a surfactant, 1 g of sodium chloride as a porogen, 1 ml of glycerol as a plasticizer, 200 ml of water as an external phase solvent, 1000 rpm for 1 hr as the stirring rate and time, and 40 0C as a drying temperature. The F15 showed good production yield (82%), loading efficiency (73%), and fast dissolution rate in 0.1 N HCl (more than 80% drug release in less than 15 min). The in vitro release study showed that F15 had significantly better release characteristic (p < 0.5) when compared to both the pure TEL and the reference commercial tablet Micardis®. Finally, one can conclude that the SP technology can be a promising alternative way for the formulation of poorly water soluble drugs, such as TEL, into immediate release formulation.Keywords: Telmisartan, Sponge like, solubility, Eudragit E100.